2009
DOI: 10.1016/j.genhosppsych.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in convalescent severe acute respiratory syndrome patients: a 4-year follow-up study

Abstract: PTSD occurs in a significant percentage of subjects who recover from SARS, and the occurrence of PTSD predicts persistent psychological distress and diminished social functioning in the 4 years after SARS treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(191 citation statements)
references
References 37 publications
8
176
2
5
Order By: Relevance
“…Our results revealed that the standard SAS scores were 46.8 in male doctors and 46.7 in female doctors respectively. In comparison with studies using the same anxiety indicator, our raw scores (37.8 in male doctors and 37.7 in female doctors) were close to the levels among survivors of severe acute respiratory syndrome, which were in the range of 37.2-43.0 at 2, 7, 10, 20 and 46 months after discharge from medical hospitalization 25) , but lower than that among airplane pilots (44.56) 26) ; on the other hand, the standard scores were much higher than the anxiety status among university teachers (37.3 in male and 34.8 in female) 27) , and even a little higher than the level (45.36) among inhabitants in Wenchuan County after the 5.12 Sichuan earthquake 28) . All these findings revealed that Chinese doctors were suffering from a considerably serious anxiety disorder at present.…”
Section: Discussionsupporting
confidence: 68%
“…Our results revealed that the standard SAS scores were 46.8 in male doctors and 46.7 in female doctors respectively. In comparison with studies using the same anxiety indicator, our raw scores (37.8 in male doctors and 37.7 in female doctors) were close to the levels among survivors of severe acute respiratory syndrome, which were in the range of 37.2-43.0 at 2, 7, 10, 20 and 46 months after discharge from medical hospitalization 25) , but lower than that among airplane pilots (44.56) 26) ; on the other hand, the standard scores were much higher than the anxiety status among university teachers (37.3 in male and 34.8 in female) 27) , and even a little higher than the level (45.36) among inhabitants in Wenchuan County after the 5.12 Sichuan earthquake 28) . All these findings revealed that Chinese doctors were suffering from a considerably serious anxiety disorder at present.…”
Section: Discussionsupporting
confidence: 68%
“…The IES-R, developed by Weiss and Marmar is a 22-item, 5-point scale (0, not at all; 1, a little bit; 2, moderately; 3, quite a bit; 4, extremely) with a Cronbach's alpha of 0.93. The IES-R Korean version yields a total score (ranging from 0 to 88) and subscale scores which can be calculated for the hyperarousal (consisting of the following items: 4, 10, 14,18,19,21), avoidance (consisting of the following items: 5,8,11,12,17,22), intrusion (consisting of the following items: 1,3,6,9,16), and sleep and numbness (consisting of the following items: 2, 7, 13, 15, 20) subscales of PTSD [10]. The internal consistency of the IES-R Korean version was 0.69-0.83 [11].…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that healthcare workers experience burnout, traumatic stress, anxiety, and depressive symptoms even after the outbreak [4]. Previous research has found that the prevalence of post-traumatic stress disorder (PTSD) was also increased among survivors of infectious diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, on the SCL-90-R, there are seven items not included in any of the nine factors, among which, three reflect sleep quality. Individual SCL-90-R factors have been used to evaluate the psychological condition of PTSD patients, and there is sufficient evidence to support the correlation of higher global SCL-90-R scores with the severity of a patient's core PTSD symptoms [12,[48][49][50][51][52][53][54][55][56][57].…”
Section: Outcome Measuresmentioning
confidence: 99%